2003
DOI: 10.1373/49.6.940
|View full text |Cite
|
Sign up to set email alerts
|

Chemiluminescence Assay Improves Specificity of Hepatitis C Antibody Detection

Abstract: Background: Antibodies to hepatitis C virus (anti-HCV) have typically been detected by enzyme immunoassay (EIA).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
43
2
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 24 publications
2
43
2
2
Order By: Relevance
“…CLIA showed significantly improved specificity, a greater positive predictive value, and a similar sensitivity compared to those of EIA for detecting anti-HCV antibodies (10,15). Although automated CLIAs are gradually replacing the EIA, there are no published studies on the comparative evaluation of automated CLIAs (10,15,16,22,27). We compared the performance of currently marketed anti-HCV automated CLIAs under routine conditions of a hospital laboratory.…”
mentioning
confidence: 99%
“…CLIA showed significantly improved specificity, a greater positive predictive value, and a similar sensitivity compared to those of EIA for detecting anti-HCV antibodies (10,15). Although automated CLIAs are gradually replacing the EIA, there are no published studies on the comparative evaluation of automated CLIAs (10,15,16,22,27). We compared the performance of currently marketed anti-HCV automated CLIAs under routine conditions of a hospital laboratory.…”
mentioning
confidence: 99%
“…Although tests are usually interpreted as positive or negative, samples with low-positive anti-HCV results are usually falsely positive, whereas Ͼ90% of samples that are high-positive are from patients who test positive for HCV RNA (8,9 ). Recently, the CDC revised guidelines for laboratories, recommending confirmatory testing for samples with low signal-to-cutoff (S/C) ratios (10 ).…”
mentioning
confidence: 99%
“…The Pathology and Laboratory Medicine Service maintains a blinded database of all patients with positive anti-HCV results; details of the screening program and the assays used have been reported previously (8,9 ). A total of 13 714 individuals were tested over a 13-month period by a third-generation EIA (Ortho Clinical Diagnostics), with 2140 (15.6%) positive, whereas 19 518 were tested over a 21-month period by CA (Vitros Eci; Ortho Clinical Diagnostics), with 2257 (11.6%) positive (Data are available in supplemental files EIA and CA in the Data Supplement that accompanies the online version of this Technical Brief at http://www.clinchem.org/content/ vol50/issue5/).…”
mentioning
confidence: 99%
“…However, lower and/or upper cut-off values for the S/Co ratio vary between studies, even for the same assay [6,7,[9][10][11]. This study provides the first results for the Elecsys Anti-HCV II assay, but further studies are necessary to confirm these findings.…”
Section: S/co Ratiomentioning
confidence: 76%
“…Results of the RecomLine HCV strip immunoassay performed in 276 samples with an S/Co ratio ≥ 1. A number of previous studies have reported the threshold S/Co ratios for a variety of anti-HCV IgG assays [6,7,[9][10][11], and the CDC has published a list of S/Co ratios predictive of a true positive result ≥ 95% of the time for six different immunoassays [1,2]. The Elecsys Anti-HCV II immunoassay was reported to have superior performance compared to several other commercially available assays [8,12].…”
Section: Discussionmentioning
confidence: 99%